Basic structural dynamics - Anderson, J. C. (James C.), 1939-; Naeim, Farzad (Hoboken, N.J. : John Wiley & Sons, 2012)
"This book is intended as a basic introduction to the topic of structural dynamics for undergraduate civil and structural engineering students. Covering single and multiple degree of freedom systems while providing an introduction to earthquake engineering, this book keeps the coverage succinct and on topic at a level appropriate for non-specialist undergraduate and graduate students. Through dozens of worked examples based on actual structures, it also introduces the students to NONLIN, a matrix analysis software package"--
Basic Structural Dynamics; Contents; Preface; Chapter 1 Basic Concepts of Structural Dynamics; 1.1 The Dynamic Environment; 1.2 Types of Dynamic Loading; 1.3 Basic Principles; 1.4 Dynamic Equilibrium; Chapter 2 Single-Degree-of-Freedom Systems; 2.1 Reduction of Degrees of Freedom; 2.2 Time-Dependent Force; 2.3 Gravitational Forces; 2.4 Earthquake Ground Motion; 2.5 Formulation of Equation of Motion; 2.5.1 d'Alembert's Principle; 2.5.2 Virtual Work (Virtual Displacements); 2.6 Generalized Coordinates; 2.6.1 Discrete Parameters; 2.6.2 Continuous Parameters; 2.6.3 Transformation Factors.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Structural dynamics -- Textbooks; TECHNOLOGY & ENGINEERING / Structural; Structural dynamics; Electronic books; Textbooks; Electronic books